Pulmonary involvement in ANCA-associated vasculitis - Durak Ediboğlu, Elif; Akyüz Dağlı, Pınar; Köksal, Deniz (Acta Medica, 2025)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) comprises systemic disorders, mainly GPA and MPA, characterized by small- and medium-vessel inflammation with frequent pulmonary involvement. Thoracic manifestations are diverse and include tracheobronchial disease, pulmonary nodules and cavitary lesions, diffuse alveolar hemorrhage, interstitial lung disease, bronchiectasis, and pleural involvement, each with distinct clinical and radiological features. Diagnostic evaluation requires integration of clinical findings, high-resolution CT, pulmonary function tests, bronchoscopy, and histopathology, while excluding infectious and malignant causes. Tuberculosis remains a major diagnostic challenge, particularly in endemic regions, due to overlapping clinical, radiological, and even serological features. Treatment typically involves high-dose glucocorticoids with cyclophosphamide or rituximab, with management tailored according to the extent and pattern of pulmonary involvement. Close monitoring is especially important in patients with MPO-ANCA positivity and interstitial lung disease, given the risk of progression to systemic vasculitis.